Profile of Multi Drug Resistant Tuberculosis patients: A Study at Drug Resistant Tuberculosis Centre in Kumaun Region, Uttarakhand - Awasthi, Sadhana; Verma, Neha; Gopal Nautiyal, Ram; Kumar Solanki, Hariom (Indian Journal of Community Health, 2020)
Background: Drug Resistant Tuberculosis (DR-TB) has frequently been encountered in India, and its presence has been known virtually from the time anti-TB drugs were introduced for the treatment of Tuberculosis. Multi Drug Resistant Tuberculosis (MDR-TB) is a man-made phenomenon and has become a formidable challenge to effective Tuberculosis control in India. Objectives: To study the Socio-demographic and Clinical profile of Multi Drug Resistant Tuberculosis (MDR-TB) patients presenting to Drug Resistant Tuberculosis (DR-TB) Centre at Govt. Medical College, Haldwani in the Kumaun region, Uttarakhand. Methodology: This study is a Record based study, where in service data available at Drug Resistant Tuberculosis (DR-TB) Centre at Govt. Medical College, Haldwani in the Kumaun region, Uttarakhand, was accessed and analyzed. Inclusion criteria included all patients with diagnosis of Multi Drug Resistant Tuberculosis (MDR-TB) presenting to the centre from 1st April 2015 to 31st December 2015. Results: The present study showed that younger age group particularly males were more affected with MDR-TB. Under-nutrition was quite prevalent among the MDR-TB patients. 56.7% cases were addicted to alcohol and 54.3% cases were addicted to smoking. 85.8% patients took treatment for TB and 44.1% not completed their treatment. Relapse of previous anti-tuberculosis treatment was found to be the major contributor in MDR-TB suspect cases. Prevalence of XDR-TB was also found to be low. Conclusion: The findings of the study emphasize the importance of studying the socio-demographic factors and baseline clinical characteristics in different MDR-TB patient categories to timely modify and strengthen the national programs.